2012
DOI: 10.3892/ijo.2012.1605
|View full text |Cite
|
Sign up to set email alerts
|

AKT serine/threonine protein kinase modulates bufalin-triggered intrinsic pathway of apoptosis in CAL 27 human oral cancer cells

Abstract: Abstract. Bufalin has been reported to induce apoptosis in a variety of cancers but little is demonstrated in oral squamous cell carcinoma (OSCC) cells. The present study investigated the inhibition of proliferation, cell cycle arrest and apoptotic effects of bufalin in CAL 27 human oral cancer cells. Bufalin inhibited the growth of CAL 27 cells in a concentration-dependent manner and an IC 50 value of bufalin was about 125 nM for 24 h treatment using the MTT assay. Moreover, the cell cycle distribution was ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…These results indicate a close relationship of the actions of bufalin in the inhibition of HCC growth and enhancement of necrosis and apoptosis in orthotopic-transplanted tumor tissue, which are related to regulation of the PI3K/Akt signaling pathway. Therefore, our results are consistent with those of previous studies showing that bufalin induces apoptosis in gastric cancer MGC803 cells and oral cancer CAL 27 cells by inhibition of the PI3K/AKT signaling pathway [10,11]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results indicate a close relationship of the actions of bufalin in the inhibition of HCC growth and enhancement of necrosis and apoptosis in orthotopic-transplanted tumor tissue, which are related to regulation of the PI3K/Akt signaling pathway. Therefore, our results are consistent with those of previous studies showing that bufalin induces apoptosis in gastric cancer MGC803 cells and oral cancer CAL 27 cells by inhibition of the PI3K/AKT signaling pathway [10,11]. …”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, bufalin has been demonstrated to induce apoptosis in gastric cancer MGC803 cells and oral cancer CAL 27 cells by inhibition of the AKT signaling pathway [10,11]. Our previous in vitro studies have shown that the mechanisms underlying the antitumor effects of bufalin in hepatoma cells appear to be mediated by AKT/GSK3β/β-catenin/E-cadherin signaling pathways [12].…”
Section: Introductionmentioning
confidence: 99%
“…The current treatments for oral cancer are inadequate and a significant proportion of oral cancer patients may develop local invasion and metastases (11). Numerous studies have been performed to find novel agents (especial from natural plant) which can trigger programmed cell death (apoptosis) in tumor cells and hopefully to provide a new therapeutic approach for anticancer design (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Bufalin has excellent antitumor effects against various solid tumors, including those associated with leukemia, osteosarcoma, gastric cancer, prostate cancer, ovarian cancer, and colon cancer. [1][2][3][4][5][6][7][8][9][10][11] Previous studies have suggested that the anticancer activity of bufalin could be attributed to its well-documented inhibition of cell proliferation, induction of apoptosis, disruption of the cell cycle, and regulation of the immune response. 12,13 Although these results are promising, the use of this single chemotherapeutic drug is far from perfected and is associated with undesirable severe side effects such as immunosuppression, damage to normal tissues, high toxicity, and development of drug resistance.…”
Section: Introductionmentioning
confidence: 99%